A CRITICISM ON MATERIALISM TOWARDS AMERICAN POPULAR CULTURE IN LORDE’S “ROYALS” - Permatasari, Gita (LANTERN (Journal on English Language, Culture and Literature), 2015)
“Royals” is a song that sung by a singer, Lorde. The lyrics tell about popular culture in America which usually portrayed as something luxurious and glamorous. The purpose of this study is to know the content of the song by analyzing the lyrics and music video of the song. The study uses intrinsic and extrinsic theories to analyze the data and library research to compile the data. Library research is used to get literary and materialism theories. The finding of this study is an understanding of materialism in American popular culture which reflected through the symbols and expression in the song “Royals”.